Perception of issues by factory workers in Malaysia : the role of media - A Manaf, Aini Maznina; Idid, Syed Arabi; Buyong, Mazni (IJAH Research Publishing, 2018)
Media have the ability to shape people’s opinion on many important issues of a country. The public’s exposure to media is likely to change their opinions towards certain issues that are widely discussed in the media. Factory workers’ perception on major issues of a country is important as it entails strong participation in the government’s programmes. In light of this concern, a study was conducted to examine the influence of media on factory workers’ opinion concerning the issues of importance that take place in Malaysia. Among objectives of the study are: a) to examine the usage of media among factory workers; b) to find out the relationship between media and their perceptions about main issues of the country; and c) to determine the relationship between media and the Prime Minister’s leadership. Findings drawn from the survey data indicate that factory workers are high users of media particularly the new media. The findings also indicate that issues from the main media did not solely influence the factory workers in their decision making of whom to vote in the general election. Since they were high users of the new media, they also have the new media as their alternative source of information. Moreover, the findings also show that credibility and reliability of the media play an important role. The respondents would only believe the news only when the sources of information were from reliable sources.